2019
DOI: 10.1675/063.042.0303
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-Level Nest Site Selection of Sympatric Piping Plovers (Charadrius melodus) and American Oystercatchers (Haematopus palliatus) in New Jersey, USA

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The slightly higher tolerance for areas with moderate vegetation that we observed in New England may also be reflected by MacIvor (1990), who found that 0.5‐m 2 plots had a mean vegetative cover of 15.2 ± 23.6% in Massachusetts. In addition, the particularly high importance of coarse‐grained or shelly substrates for Piping Plovers is also evident in localized studies in Massachusetts (MacIvor 1990, Jones 1997), New Jersey (Burger 1987, Maslo et al 2011, Grant et al 2019), and Maryland (Patterson 1988). In contrast with our results, a study on Long Island (Cohen et al 2008) suggested that predominantly sandy substrates were preferred.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The slightly higher tolerance for areas with moderate vegetation that we observed in New England may also be reflected by MacIvor (1990), who found that 0.5‐m 2 plots had a mean vegetative cover of 15.2 ± 23.6% in Massachusetts. In addition, the particularly high importance of coarse‐grained or shelly substrates for Piping Plovers is also evident in localized studies in Massachusetts (MacIvor 1990, Jones 1997), New Jersey (Burger 1987, Maslo et al 2011, Grant et al 2019), and Maryland (Patterson 1988). In contrast with our results, a study on Long Island (Cohen et al 2008) suggested that predominantly sandy substrates were preferred.…”
Section: Discussionmentioning
confidence: 96%
“…Histograms showing the frequency of Piping Plover nests (used resource units) and associated leastcost path distances to low-energy shorelines with moist substrates (distance to MOSH). (MacIvor 1990, Jones 1997, New Jersey (Burger 1987, Maslo et al 2011, Grant et al 2019, and Maryland (Patterson 1988). In contrast with our results, a study on Long Island (Cohen et al 2008) suggested that predominantly sandy substrates were preferred.…”
Section: Range-wide Habitat Selection Patternsmentioning
confidence: 99%